Application of Indocyanine Green in Flap Surgery: A Systematic Review - Li, Ke; Zhang, Zheng; Nicoli, Fabio; D'Ambrosia, Christopher; Xi, Wenjing; Lazzeri, Davide; Feng, Shaoqing; Su, Weijie; Li, Hua; Ciudad, Pedro; Tremp, Mathias; Zhang, Yi Xin (Journal of Reconstructive Microsurgery, 2018)
Background The vascularization of the distal portions of transferred tissue represents the most critical factor in the success of reconstructive surgery. In recent years, indocyanine green (ICG) fluorescence imaging techniques have been applied during surgery to evaluate flap perfusion. However, this investigation has found that there is little consensus regarding the standard dose of ICG as well as the pre-operative requirements of ICG allergy testing. The aim of this study is to summarize the applications of ICG to tissue transfers and safe dosing practices and to provide insight to the possible adverse effects of ICG on flap surgery with the goal of helping clinicians apply ICG safely and efficiently to tissue transfer procedures.Methods A literature search was performed using, Wiley InterScience, and Springer with the key words, ‘Flap,’ ‘indocyanine green,’ ‘surgery,’ and related mesh words for all publications between 2005 and 2015. Title and abstract screening was performed using predefined in- and exclusion criteria.Results Seventy-three articles were included. These were classified as “application of ICG in flap surgery” and “the security of applying ICG in flap surgery”.Conclusions ICG fluorescence imaging preoperatively facilitates the detection of perforators in tissue flaps with thickness <20 mm, aids in the evaluation of flap microcirculation and perfusion, and allows surgeons to select dominant cutaneous nerves while evaluating the quality of vascular anastomoses and locating thromboses. The literature also concluded that potential allergic reactions to ICG should be taken into consideration.
Keywords: indocyanine green; fluorescence imaging; flap surgery